Adverse events following HPV immunization in Australia: Establishment of a clinical network. Issue 10 (2nd October 2016) - Crawford, Nigel W.; Hodgson, Kate; Gold, Mike; Buttery, Jim; Wood, Nicholas; ,
ABSTRACT: Objective : To formalise a collaborative national Adverse Events Following Immunisation Clinical Assessment Network (AEFI-CAN) following the expansion of the Australian Human Papillomavirus (HPV) immunisation program to boys in 2013.Methods : AEFI-CAN linked state-based vaccine safety clinics and the Department of Health including the Therapeutic Goods Administration (TGA). Monthly teleconferences held to discuss HPV related cases. AEFI conditions of interest recorded in a centralised database.Results : Between 1 st January 2013 - 31 st October 2014, 118 HPV AEFI were documented, 56% in males. The median age was 13 y (range 12–16 years). The majority of AEFI reports were after dose 1 (59%). 76 of 118 (64%) AEFI were seen in a vaccine safety clinic: 62% in Victoria, NSW (16%), South Australia (9%) and Western Australia (8%). Eight TeleHealth consultations were undertaken. AEFI were categorised as: rash 24% of reports (n = 28), urticaria/angioedema 23% (n = 27), anaphylaxis 3% (n = 4). Syncope was also reported (n = 12, 10%) and other neurological events (n = 22, 19%).Conclusions : We demonstrated the advantages of a national network, providing a collaborative approach to AEFI review and management. The vaccine safety network has applicability to any vaccination program, and has potential to collaborate more broadly with regional pharmacovigilance partners such as New Zealand.